2023
DOI: 10.3390/metabo13111159
|View full text |Cite
|
Sign up to set email alerts
|

The Dose–Response Effect of Fluoride Exposure on the Gut Microbiome and Its Functional Pathways in Rats

Zhe Mo,
Jian Wang,
Xinyue Meng
et al.

Abstract: Metabolic activities within the gut microbiome are intimately linked to human health and disease, especially within the context of environmental exposure and its potential ramifications. Perturbations within this microbiome, termed “gut microbiome perturbations”, have emerged as plausible intermediaries in the onset or exacerbation of diseases following environmental chemical exposures, with fluoride being a compound of particular concern. Despite the well-documented adverse impacts of excessive fluoride on va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…The risk of developing fluorotic lesions of enamel due to the ingestion of recommended levels of fluoride during amelogenesis has been deemed acceptable when compared to the anticaries benefits of fluoride [ 53 , 64 ]. However, excessive fluoride intake can have negative effects on thyroid function, the skeletal system, the reproductive system, and cardiovascular health [ 65 , 66 , 67 ]. The risk of fluorosis depends on the dose, duration, and timing of fluoride exposure during tooth enamel formation [ 53 , 68 ].…”
Section: Fluorosis Risk From Systemic Fluoridementioning
confidence: 99%
“…The risk of developing fluorotic lesions of enamel due to the ingestion of recommended levels of fluoride during amelogenesis has been deemed acceptable when compared to the anticaries benefits of fluoride [ 53 , 64 ]. However, excessive fluoride intake can have negative effects on thyroid function, the skeletal system, the reproductive system, and cardiovascular health [ 65 , 66 , 67 ]. The risk of fluorosis depends on the dose, duration, and timing of fluoride exposure during tooth enamel formation [ 53 , 68 ].…”
Section: Fluorosis Risk From Systemic Fluoridementioning
confidence: 99%
“…In addition, using high-throughput 16S rRNA gene sequencing technology, it has been found that fungi may be one of the important factors affecting intestinal function, and excessive fluorine can affect the species richness of intestinal fungi in mice, suggesting that fluorine may cause adverse intestinal symptoms by causing an imbalance in the intestinal fungal population, thus affecting the normal intestinal function ( 81 , 82 ). Moreover, fluoride exposure not only disturbed the compositional balance of the gut microbiome, but also triggered metabolic disorders ( 83 ). Alterations in intestinal microbiota and metabolome play a critical role in regulating disease susceptibility and multi-organ damage after excessive fluoride exposure ( 73 ).…”
Section: Effects Of Fluoride On Immune Organsmentioning
confidence: 99%